Virtual capacitance meter based on ratio-metric voltage measurement for sensor testing. (2021) - Lata, Suman; Verma, H.K.
Abstract: This paper presents design, implementation and evaluation of a Virtual Capacitance Meter (VCM) for testing capacitive sensors. It is based on the novel concept of ratio-metric voltage measurement. Two different approaches, namely, Reference Capacitor Approach (RCA) and Reference Resistor Approach (RRA) have been presented in the paper. The implementation has been done in LabVIEW 13.0 and USB 6221 card has been used for data acquisition. In the virtual instrument (VI) a radio button control has been used for the selection between RCA and RRA modes. The accuracy of capacitance measurement using the proposed VCM, depends mostly on the accuracy of the reference component, namely, reference capacitor or reference resistor. The errors in voltage measurement are nullified because of the ratio-metric approach. Other factors contribute very little to the accuracy of the measurement. In case reference capacitor of high accuracy is available, RCA method should be preferred out of the two approaches. For the measurement of very large capacitance, lower frequency cards like USB 6008 can be used. However, for the measurement of very small capacitance, high frequency cards like USB 6221 will be required.